Pola Komunikasi Interpersonal Orang Tua terhadap Anak Pecandu Game Online di Kelurahan Pengawu Kota Palu - Kristi, Inka (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2025)
This research aims to determine the interpersonal communication patterns of parents towards children who are addicted to online games in the Pengawu sub-district, Palu City. This type of research is descriptive qualitative, namely making descriptions systematically, factually and accurately. The research concept leads to four Mc family communication patterns. Leod and Chaffee on the theory of first generation family communication patterns. The subjects or informants chosen in this research consisted of four (4) families of informants. Data collection was carried out through observation and in-depth interviews.The results of the research show that the interpersonal communication patterns of parents towards children addicted to online games in Pengawu Village, Palu City vary. The Laissez-Faire pattern, in which parents are passive and do not limit the child's play habits, depends on the child. In contrast, a firm Protective pattern, with consistent rules, helps control addiction. Some families shift from a Protective to a Laissez-Faire pattern as a result of conflict, indicating adaptation to the child's developing addiction